Company-specific characteristics and the choice of hedge accounting for derivatives reporting: Malaysian case - Abdullah, Azrul; Ku Ismail, Ku Nor Izah (Inderscience Publishers, 2017)
This study investigates the choice of applying hedge accounting among Malaysian listed companies in reporting their use of derivatives for hedging activities.Based on a sample of 300 Malaysian listed companies, we found that only 162 companies (54%) use derivatives to hedge their financial risk exposure and only 30% of those companies choose to apply hedge accounting.In addition, this study examines the relationship between company-specific characteristics and the choice to apply hedge accounting.The logistic regression results show that the decision to apply hedge accounting by Malaysian companies is positively influenced by company size and leverage. The implications of the findings are discussed and some conclusions are drawn.